Association of Increased Remnant Cholesterol and the Risk of Coronary Artery Disease: A Retrospective Study - Kexin, Wang; Yaodong, Ding; Wen, Gao; Rui, Wang; Jiaxin, Yang; Xiaoli, Liu; Hua, Shen; Hailong, Ge (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims Low-density lipoprotein cholesterol (LDL-C) is the primary target in lipid-lowering therapy in coronary artery disease (CAD). But some patients with normal levels of LDL-C still suffer from CAD progression and malignant outcomes (e.g., MACEs), and the mechanism is unclear. Previous prospective studies demonstrated that remnant cholesterol (RC) and non-HDL-C were capable to predict the risk of CAD. This study evaluated the association between RC and non-HDL-C with the risk of CAD. Methods 12,563 patients were enrolled in our study. We categorized patients into four concordance/discordance groups according to the median of RC, LDL-C and non-HDL-C. Then we performed a propensity score matching (PSM) strategy. Unadjusted and adjusted multivariate logistic regression models were used to evaluate the relationship between lipid concentrations. Results 8,658 (68.9%) patients were male with a median age of 61 (54,67) years. The multivariate logistic regression showed the OR of RC was 1.952 (CI=1.276-2.988, p＝0.002). The OR of low RC/high LDL-C group was 0.574 (CI=0.462-0.714, p＜0.001) and the OR of low RC/high non-HDL-C group was 0.574 (CI=0.462-0.714, p＜0.001). The p for interaction between RC and hypertension, diabetes were both <0.001. Conclusions Our study showed a significant association between RC and CAD. The level of RC was more capable to reflect the risk of CAD than LDL-C and non-HDL-C. There was an interaction relationship between remnant cholesterol and age, gender, hypertension, diabetes in CAD. But we didn’t find whether there was a relationship between non-HDL-C and CAD.